The Involvement of Danger-Associated Molecular Patterns in the Development of Immunoparalysis in Cardiac Arrest Patients. Issue 11 (November 2015) - Timmermans, Kim; Kox, Matthijs; Gerretsen, Jelle; Peters, Esther; Scheffer, Gert Jan; van der Hoeven, Johannes G.; Pickkers, Peter; Hoedemaekers, Cornelia W.
Abstract : Objectives: After cardiac arrest, patients are highly vulnerable toward infections, possibly due to a suppressed state of the immune system called "immunoparalysis." We investigated if immunoparalysis develops following cardiac arrest and whether the release of danger-associated molecular patterns could be involved. Design: Observational study. Setting: ICU of a university medical center. Patients: Fourteen post–cardiac arrest patients treated with mild therapeutic hypothermia for 24 hours and 11 control subjects. Measurements and Main Results: Plasma cytokines showed highest levels within 24 hours after cardiac arrest and decreased during the next 2 days. By contrast, ex vivo production of cytokines interleukin-6, tumor necrosis factor-α, and interleukin-10 by lipopolysaccharide-stimulated leukocytes was severely impaired compared with control subjects, with most profound effects observed at day 0, and only partially recovering afterward. Compared with incubation at 37°C, incubation at 32°C resulted in higher interleukin-6 and lower interleukin-10 production by lipopolysaccharide-stimulated leukocytes of control subjects, but not of patients. Plasma nuclear DNA, used as a marker for general danger-associated molecular pattern release, and the specific danger-associated molecular patterns (EN-RAGE and heat shock protein 70) were substantially higher in patients at days 0 and 1 compared with control subjects. Furthermore, plasma heat shock protein 70 levels were negatively correlated with ex vivo production of inflammatory mediators interleukin-6, tumor necrosis factor-α, and interleukin-10. Extracellular newly identified receptor for advanced glycation end products-binding protein levels only showed a significant negative correlation with ex vivo production of interleukin-6 and tumor necrosis factor-α and a borderline significant inverse correlation with interleukin-10. No significant correlations were observed between plasma nuclear DNA levels and ex vivo cytokine production. Interventions: None. Conclusions: Release of danger-associated molecular patterns during the first days after cardiac arrest is associated with the development of immunoparalysis. This could explain the increased susceptibility toward infections in cardiac arrest patients.